220 Is Multifactorial Risk Assessment a Team Sport? Disciplinary Differences in Perceived Acceptability and Feasibility of a Community-based Fall Prevention Service. (16th September 2019) - McHugh, Sheena; Cronin, Finola; Moriarty, Eileen; Turvey, Spencer; Barry, Patrick; O'Connor, Kieran; Timmons, Suzanne; M Kearney, Patricia
Abstract: Background: Multifactorial falls risk assessment is an evidence-based practice recommended to prevent falls among older people. Previous research has identified cultural,  practical and professional challenges to implementing complex fall prevention interventions. Fall prevention interventions are frequently delivered by multidisciplinary teams (MDTs). This requires multiple health professionals, who practice under different professional norms and governance structures, to accommodate new ways of working. Our aim is to explore disciplinary differences in the perceived acceptability, appropriateness and feasibility of community-based multifactorial falls risk assessment clinics during initial implementation. Methods: A mixed methods study is being conducted with analysis of administrative data on delivery of risk assessments (2016-2018), and semi-structured interviews staff involved in multidisciplinary teams (physiotherapists (PT, n=5), occupational therapists (OT, n=6), and public health nurses (n=4)]. Interviews were conducted prior to implementation and at 6 months (n=30 interviews total). Framework-driven thematic analysis was used to identify factors influencing implementation and explore perceptions of acceptability, appropriateness and feasibility. Results: Implementation varied across disciplines; 28% of assessments were conducted by nurses (n=83), 36% (n=111) by physiotherapists, and 36% (n=108) by OTs. Preliminary qualitative analysis suggests that OTs welcomed the opportunity to expand their scope of practice. Conducting assessments at set times in static clinics was incompatible with public health nurses' workflow. Their limited availability and time-sensitive competing priorities were barriers to the feasibility of an MDT-approach. Physiotherapists questioned the relative advantage of a broad assessment, and whether it was an appropriate use of resources given waiting lists for physiotherapy intervention. Data analysis is ongoing. Conclusion: The study results have already been used to inform service adaptations including the introduction of dedicated intervention sessions. Training and implementation support for multidisciplinary teams may need to be tailored to the needs of different professional groups to enhance adoption and fidelity.